Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/cncy.22135
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Milan System for Reporting Submandibular Gland Cytopathology: An international, multi‐institutional study

Abstract: BACKGROUND:The Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) is a 6-tier diagnostic category system with associated risks of malignancy (ROMs) and management recommendations. Submandibular gland fineneedle aspiration (FNA) is uncommon with a higher frequency of inflammatory lesions and a higher relative proportion of malignancy, and this may affect the ROM and subsequent management. This study evaluated the application of the MSRSGC and the ROM for each diagnostic category for 734 submandibu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
67
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 48 publications
13
67
2
1
Order By: Relevance
“…In the present work, the cause of ROM in the benign neoplasm category was attributed to the presence of a case of low grade epithelial myoepithelial carcinoma on surgical follow-up that was cytologically misinterpreted as pleomorphic adenoma (false negative case). The reported ROM in other studies is caused by false negative interpretation predominantly of carcinoma ex pleomorphic adenoma (1,2) followed by low grade mucoepidermoid carcinoma (13,14), adenoid cystic carcinoma (9,14), epithelial myoepithelial carcinoma (14) and oncocytic carcinoma (13). Epithelial myoepithelial carcinoma can pose a diagnostic complexity to the cytopathologist.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the present work, the cause of ROM in the benign neoplasm category was attributed to the presence of a case of low grade epithelial myoepithelial carcinoma on surgical follow-up that was cytologically misinterpreted as pleomorphic adenoma (false negative case). The reported ROM in other studies is caused by false negative interpretation predominantly of carcinoma ex pleomorphic adenoma (1,2) followed by low grade mucoepidermoid carcinoma (13,14), adenoid cystic carcinoma (9,14), epithelial myoepithelial carcinoma (14) and oncocytic carcinoma (13). Epithelial myoepithelial carcinoma can pose a diagnostic complexity to the cytopathologist.…”
Section: Discussionmentioning
confidence: 95%
“…Rossi et al (7) reported an allowed range of 10% to 15% for this category's incidence. However in some reports, the rate reached up to 44% (12) or 50 % (9). The cause of these wide variations in the incidence of the non-diagnostic category between different studies might be related to the fact that the adequacy of FNA materials of the salivary gland lesions had no definite criteria and was widely related to variable quantitative and qualitative restrictions for a long period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Results of several studies that analysed distribution of cases and estimated ROM in each MSRSGC category show that FNA cytology is an effective diagnostic procedure and confirmed the validity and diagnostic utility of MSRSGC, further revealing that ROMs of each category were broadly in line with those suggested in MSRSGC. In some of these studies, higher ROM for AUS category than in MSRSGC was observed, which probably resulted from the lower number or heterogeneity of AUS patients in these studies …”
Section: Diagnostic Accuracy Of Cytopathology For Salivary Gland Lesimentioning
confidence: 92%
“…Moreover, as presented in reports listed in Table and other studies in the literature, a, small number of WT cases, especially WT metaplastic variant with mild or marked nuclear atypia of cells, can be defined as other MSRSGC diagnostic categories . Thus, WTs with mild or marked nuclear atypia of cells could be classified as category 3—AUS with 20% ROM, as category 4B—salivary gland neoplasm of uncertain malignant potential with 35% ROM, as category 5—suspicious for malignancy with 60% ROM for finding a malignant tumour by histology, or even as category 6—malignant (Table ) .…”
Section: Diagnostic Accuracy Of Cytopathology For Salivary Gland Lesimentioning
confidence: 99%
“…The field of cytopathology successfully implemented standardized reporting with the initial version of the Bethesda System for Reporting Cervical Cytology over 20 years ago and its subsequent updates . Updated terminology reporting systems have also been introduced for cytologic sample reporting in the thyroid, pancreas, urine, salivary gland, and breast as well . As we enter a new decade, the latest effort for improving reporting has gained momentum to incorporate serous fluids in a standardized format .…”
mentioning
confidence: 99%